Carboplatin‐induced severe hypersensitivity reaction: Role of IgE‐dependent basophil activation and FcεRI. Issue 11 (5th November 2014) - Iwamoto, Takuya; Hirai, Hiroyuki; Yamaguchi, Nozomi; Kobayashi, Natsuki; Sugimoto, Hiroko; Tabata, Tsutomu; Okuda, Masahiro
<x xml:space="preserve">Abstract</x> Basophil activation was observed in patients with a history of carboplatin‐induced severe hypersensitivity reaction (HR). However, the precise mechanism by which carboplatin induces basophil activation and the associated surrogate markers remains to be elucidated. To investigate whether IgE‐dependent mechanisms, including the overexpression of FcεRI, participate in carboplatin‐induced basophil activation, 13 ovarian cancer patients were enrolled: 5 with a history of carboplatin‐induced severe hypersensitivity reaction within the past 2 years, and 8 with no such history. The expression levels of FcεRI, IgE, and CD203c on basophils were measured using a flow cytometer. Immunoglobulin E‐dependent basophil activation was evaluated by testing for IgE passive sensitization using lactic acid, and by testing for phosphatidylinositol 3‐kinase inhibition, using wortmannin. In three patients positive for carboplatin hypersensitivity, pretreatment with wortmannin almost completely inhibited carboplatin‐induced basophil activation (P < 0.05). In a healthy control subject, whose own IgE showed no response to carboplatin, acquired reactivity to carboplatin when exposed to plasma from patients positive for carboplatin hypersensitivity. This did not occur when the same experiment was carried out using plasma from the patients negative for carboplatin hypersensitivity. Moreover, pretreatment with omalizumab, a monoclonal anti‐IgE antibody, almost completely blocked carboplatin‐induced basophil activation in the plasma of patients positive for carboplatin hypersensitivity. On further investigation, the HR‐positive group had significantly higher levels of FcεRI compared with the negative group (P < 0.05). In conclusion, an IgE‐dependent mechanism incorporating FcεRI overexpression participates in carboplatin‐induced severe HR. These results establish the relevance of monitoring the pharmacodynamic changes of basophils to prevent carboplatin‐induced severe HR.